Exploring platelet lysate hydrogel-coated suture threads as biofunctional composite living fibers for cell delivery in tissue repair - Costa-Almeida, R. (2019)
To engineer functional tissue substitutes, it is required a multi-component, multi-scale approach that combines both physical, chemical and biological cues. Fiber-based techniques have been explored in the field of tissue engineering to produce structures recapitulating tissue architecture and mechanical properties. In this work, we engineered biofunctional composite living fibers (CLF) as multi-compartment fibers with a mechanically competent core and a hydrogel layer. For this purpose, commercial silk suture threads were coated with a platelet lysate (PL) hydrogel by first embedding the threads in a thrombin solution and then incubating in PL. The fabrication set-up was optimized and the biological performance was studied by encapsulating human adipose-derived stem cells (hASCs). The developed coating process rendered CLF with a homogenous PL hydrogel layer covering suture threads. Encapsulated hASCs were viable up to 14 days in culture and were able to align at the surface of the core fiber and deposit collagen types I and III. In summary, the study shows that PL-hASCs hydrogel coated suture threads represent a simple multi-compartment and multifunctional system, with PL hydrogel offering biofunctionality to guide the biological activities of encapsulated cells in addition to the replication of tissue-level mechanical support provided by the suture threads.